El error inexcusable y el prevaricato frente a la tutela efectiva y la seguridad jurídica de la víctima y el procesado. - García Meléndez, Pablo Filiberto (2024)
In this research work, what is sought is to delimit the legal course that awaits the procedural subjects within a trial; For this purpose, a thorough study is carried out based on the objectivity of the motivation in the sentences of the administrators of justice, when resolving aspects related to compliance with the rights of the procedural parties, which may be susceptible to violation. In addition, the importance of studying and understanding the delimitation of the procedural development is added, when a judge makes a decision within a case; Therefore, the research is based on the study of rulings of the Constitutional Court regarding issues that involve the application of inexcusable error and malfeasance in the administration of justice. Consequently, a fundamental aspect of this study is based on the repercussions of the commission of some type of inexcusable error by an administrator of justice in any procedure; because from this a large number of violations of fundamental rights of the procedural subjects emerge, such as: the right to due process, effective judicial protection, among others. Therefore, the problem that arises in this investigation is: How does the declaration of inexcusable error and prevarication affect the effective protection and legal security of the victim and the defendant? Taking into account that this circumstance opens a complicated situation within the judicial system, since it affects issues related to the implementation of the constitutional principles of the state that guarantees rights. 12 The general objective of this research is to legally and dogmatically analyze the figure of inexcusable error, the criminal type of prevarication, its impact on effective judicial protection and legal security in the procedural subjects. The methodology used is based on the qualitative study of information, collecting that which needs to be susceptible to analysis to prepare a comparison and collection of data that serve for its development; important tools that yield clear conclusions regarding the investigation. Keywords: Prevarication, inexcusable error, motivation, procedural subjects, procedural direction.